2003
DOI: 10.1152/physrev.00022.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Amino Acid and Glucose Transporters in Endothelial and Smooth Muscle Cells

Abstract: While transport processes for amino acids and glucose have long been known to be expressed in the luminal and abluminal membranes of the endothelium comprising the blood-brain and blood-retinal barriers, it is only within the last decades that endothelial and smooth muscle cells derived from peripheral vascular beds have been recognized to rapidly transport and metabolize these nutrients. This review focuses principally on the mechanisms regulating amino acid and glucose transporters in vascular endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
325
0
7

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 380 publications
(352 citation statements)
references
References 616 publications
18
325
0
7
Order By: Relevance
“…Consistent with previous studies [6], we found GLUT-1 in endothelial cells. We also found that it is asymmetrically distributed, with a greater abundance on the abluminal side.…”
Section: Glut-1supporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous studies [6], we found GLUT-1 in endothelial cells. We also found that it is asymmetrically distributed, with a greater abundance on the abluminal side.…”
Section: Glut-1supporting
confidence: 93%
“…Most studies have focused on the mechanism by which elevated intracellular glucose induces endothelial dysfunction [4,5]. It is only recently that the regulation of glucose transport in endothelial cells has been examined [6], and most of this work has been on the blood-brain and blood-retina barriers [7,8,9]. The integrity of endothelial cells of small contractile vessels is also affected by hyperglycaemia, and the coronary arteries are among the most susceptible to atheroma, but few studies have directly examined glucose transporters in these vessels [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, use of simple drugs such as aspirin may influence endothelial function in hypertension. 3,4 Endothelial cells also facilitate the transport of glucose by GLUT, 5 mainly present in brain barrier, of amino acids (such as L-arginine, a substrate for nitric oxide (NO)). Recent data even suggest a relationship of the endothelium to angiogenesis.…”
mentioning
confidence: 99%
“…10 Finally, endothelial cells are also intimately involved in haemostasis and coagulation by the production of substances such as tissue factor pathway inhibitor, thrombomodulin, endothelial protein C receptor and von Willebrand factor. 5 Of particular interest, in the pathophysiology of the endothelium, is the endothelial regulation of vascular tone. 2 Endothelial cells produce several vasoactive substances, and among them is NO, the most powerful vasodilator.…”
mentioning
confidence: 99%